2001
DOI: 10.1161/01.cir.103.10.1465
|View full text |Cite
|
Sign up to set email alerts
|

Increased Wave Break During Ventricular Fibrillation in the Epicardial Border Zone of Hearts With Healed Myocardial Infarction

Abstract: A selective increase in wave break and alteration of reentry occur in the EBZ during VF in hearts with healed myocardial infarction. Increased wave break in the EBZ is compatible with the action potential duration restitution hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…However, Xie et al 3 demonstrated in a recent computational study using an anatomically realistic model of the heart that even in the presence of anatomic heterogeneities such as regional differences in fiber orientation, the role of APD restitution in the development of VF remained intact, in that steep restitution was necessary for the disintegration of a single spiral wave into multiple wavelets. In agreement with this computermodeling study, Ohara et al 27 demonstrated in a canine model of chronic myocardial infarction that increased wave break in the epicardial border zone of the infarct is compatible with the APD restitution hypothesis. They found that the dynamic APD restitution curve in the epicardial border zone of the infarct had longer DIs over which the slope was Ͼ1.…”
Section: Fixed Versus Dynamic Heterogeneities As a Cause Of Wave Breaksupporting
confidence: 79%
“…However, Xie et al 3 demonstrated in a recent computational study using an anatomically realistic model of the heart that even in the presence of anatomic heterogeneities such as regional differences in fiber orientation, the role of APD restitution in the development of VF remained intact, in that steep restitution was necessary for the disintegration of a single spiral wave into multiple wavelets. In agreement with this computermodeling study, Ohara et al 27 demonstrated in a canine model of chronic myocardial infarction that increased wave break in the epicardial border zone of the infarct is compatible with the APD restitution hypothesis. They found that the dynamic APD restitution curve in the epicardial border zone of the infarct had longer DIs over which the slope was Ͼ1.…”
Section: Fixed Versus Dynamic Heterogeneities As a Cause Of Wave Breaksupporting
confidence: 79%
“…Other parameters are the same as in the original LR1 model (28). At this parameter setting, the baseline conduction velocity is 0.55 m/s, action potential duration (APD) is shortened to 200 ms from 360 ms in the original model, and the APD restitution curve is similar to those measured from animal experiments (17,33). One important consequence of this modification is that spiral wave breakup leading to spatiotemporal chaos or multiple-wavelet fibrillation occurs in homogeneous 2-D tissue with an average cycle length of 103 ms (41,43).…”
Section: Mathematical Modelmentioning
confidence: 99%
“…All in vivo recordings have been localized to specific regions in the ventricles. [7][8][9][10][11][12][13] To date, there has been little in vivo, whole-heart analysis performed under pathological conditions known to predispose to VF.…”
mentioning
confidence: 99%